Microbial oil production from various carbon sources by newly isolated oleaginous yeasts. Issue 3 (21st November 2016) - Maina, Sofia; Pateraki, Chrysanthi; Kopsahelis, Nikolaos; Paramithiotis, Spiros; Drosinos, Eleftherios H.; Papanikolaou, Seraphim; Koutinas, Apostolis
Abstract : Microbial oil production has received significant attention as a potential precursor for the production of biofuels, oleochemicals and food products. In this study, six oleaginous yeasts, isolated from fruits, were selected based on their ability to accumulate high intracellular content of microbial oil (20–48% w/w of total dry weight). The highest content of saturated fatty acids was 68.7% (w/w), whereas the highest content of oleic acid was 62.7% (w/w). Furthermore, nutrient‐rich hydrolysates produced via enzymatic hydrolysis of flour‐rich waste streams generated by a confectionery industry were evaluated as fermentation media for microbial oil production via fed‐batch bioreactor cultures using one of the most promising isolates, namely VV_D4. A total dry weight of 40 g/L with a microbial oil content of 39% (w/w) was produced by isolate VV_D4. Critical biodiesel properties were estimated based on the fatty acid composition and correlated with the international standards. The microbial oil produced by the new isolates could be potentially used for biodiesel production.